Cost Modeling of Road Maintenance Using the Cost Significant Method in Disaster Prone Areas of Solok Regency - Lucky Ramanur Sukandar; P Purnawan; Elsa Eka Putri (Universitas Islam Sultan Agung, 2026)
This study aims to develop cost model for a periodic road maintenance project. The background is the lack of a simple and accurate calculation method to estimate the cost of the work. The model was developed using the Cost Significant Model (CSM) method and multiple linear regression, using historical data of periodic road maintenance work contracts at the Public Works and Spatial Planning Agency (DPUPR) of Solok Regency for the period 2018–2023. The analysis results show that the most significant work on the project cost is K-175 shoulder concrete, Class A Aggregate Foundation Layer (LPA), and Asphalt Concrete-Wearing Course (AC-WC). The resulting cost estimation model is Y = 4,531.24 + 1.19 X₁₄ + 1.35 X₁₅ + 1.43 X₁₉, with Y as the project cost per m², X₁₄ the price of K-175 shoulder concrete per m², X₁₅ the price of Class A LPA per m², and X₁₉ the price of AC-WC per m². This model has an average CMF value of 1.004 and a model deviation of 2.965%, much more accurate than the estimation method currently used by the Highways Division of the DPUPR of Solok Regency which has an average deviation of 29.951%. Thus, the developed CSM model is proven to be more accurate and suitable for estimating the costs of periodic road maintenance projects in Solok Regency.